Микроэлементология 21-го столетия – вызовы и решения (по итогам съездов и конференций) - Шафран, Л.М. (Актуальні проблеми транспортної медицини, 2014)
В представленном научном обзоре проведен анализ наиболее научно и
практически значимых событий 2014
года в области микроэлементологии,
изучающей содержание, биологическую роль и механизмы участия микроэлементов в жизнедеятельности живых
организмов, а также многочисленные
функциональные нарушения и заболевания, получившие наименование микроэлементозов.
Хотя микроэлементы привлекают
к себе внимание и широко используются человечеством в пищевых, лечебнопрофилактических и технологических
целях на протяжении тысячелетий, накопленный даже за последнее столетие
огромный объем информации носит
разнородный и преимущественно разрозненный характер. Оформление микроэлементологии (МЭ) в самостоятельную научную дисциплину началось
сравнительно недавно (не более 50 лет
тому назад), хотя ее фундамент как
биогеохимического научного направления был заложен работами В.И. Вернадского и его школы уже в начале ХХ
века.
Перед МЭ стоит много нерешенных вопросов, ответы на которые можно получить лишь при условии интеграции сил, средств и возможностей ее
до сего времени неоправданно обособленных ведущих направлений,
прежде всего, медицинской, ветеринарной и пищевой МЭ. Именно на решение этой задачи в плане обмена
информацией, нахождения общих позиций и преодоления различий в критериально-методических подходах
были направлены усилия организаторов и участников трех международно
значимых научно практических форумов, состоявшихся в течение 2014
года. В хронологическом порядке охарактеризованы: 15-th Internftional
Symposium on Trace Elements in Man
and Animals. June 22-26, 2014. Orlando,
Florida, USA; Международная научно-практическая конференция “Микроэлементы в медицине, ветеринарии, питании: перспективы сотрудничества и
развития”, которая состоялась 24-26
сентября 2014 г. в г. Одессе, Украина и
4-й съезд Российского общества медицинской элементологии – состоялся в
г. Ярославле (Россия) 13-14 октября
2014 г. In the present scientific review is
analyzed the most scientifically and
practically significant events of 2014 in
the field of microelementology – the
scientific discipline studying the content,
the biological role of trace elements and
mechanisms for their participation in the
activity of living organisms, as well as
numerous functional disorders and
diseases, received the name
microelementoses.
Although trace elements attract
attention and are widely used by mankind
in the food, medical and technological
purposes for thousands of years,
accumulated over the past century, even
huge amount of information is diverse
and largely uncoordinated.
Microelementology (ME) became status
of an independent scientific discipline
only in the recent decades (not more than
50 years ago), although its foundation as
biogeochemical research direction was
founded by VI Vernadsky and his school
in the early twentieth century.
There are a lot of unresolved by ME
questions, the answers to which can be
obtained only through the integration of
forces, resources and capabilities on
leading trends, primarily in the medical,
veterinary and food ME. The solution of
these problem in terms of sharing
information, finding common ground and
overcome the differences in the criteria
and methodological approaches were the
the goal and direction of efforts of the
organizers and participants of the three
internationally significant scientific forums
held during 2014. In chronological order
in this review are characterized: the 15-th Internftional Symposium on Trace
Elements in Man and Animals. June 22-26, 2014. Orlando, Florida, USA;
International scientific and practical
conference “Trace elements in medicine,
veterinary medicine, nutrition: the
prospects for cooperation and
development”, which took place on 24-26 September 2014 in Odessa, Ukraine
and the 4th Congress of the Russian
Society of Medical elementology — took
place in the city of Yaroslavl (Russia), 13-14 October 2014.
The analysis showed the presence
of the growing interest of the world
scientific community to the problems of
ME, a progressive increase in the number
held in various countries studies of the
different scientific novelty, theoretical and
practical importance, that should be used
not only in medical and economic, but the
other areas, including food and
pharmaceutical industries, agroveterinary complex, solutions of
environmental problems in the
foreseeable future. Interregional and
international cooperation in this field is
already producing tangible results.